A Parable Frame-up and Its Audacious Reframing - Curkpatrick, Stephen (New Testament studies, 2003)
Citing the difficulties of establishing a unity between parable and frame in Luke 18.1–8, this article argues that Luke has significant themes of justice and social transformation that could be used to frame the parable of the audacious widow (18.2–5). In the antecedent source of Luke's widow tradition, the widow is characteristically without a voice in her community. Ironically, Luke has effectively silenced the story's prophetic voice for justice with the parable's frame. However, the parable can find its voice through alternative framing within the gospel, for example, the Magnificat. If the parable (vv. 2–5) has independent force within the same community of the gospel's production, what possible tensions does a widely acknowledged dissonance in vv. 1–8 reflect at its point of production? What implications might these tensions have for subsequent parable interpretation?